Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Indigodole E from Strobilanthes cusia exhibits anti-IL-17A effect - Chia-Lin Lee; Chien-Ming Wang; Hung-Rong Yen; Ying-Chyi Song; Chao-Jung Chen (Natural Product Research, 2022)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Effects of Ran-GTP/importin β inhibition on the meiotic division of porcine oocytes - Yijing He; Jia Li; Lei Peng; Qiao Li; Yajie Chu; Qixin Lin; Jianjun Dai; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

A new numerical model of ring shear tester for shear band soil considering friction-induced thermal pressurization - Neng-hao Zhao; Kun Song; Rong-tang Zhang; Qing-lin Yi (Journal of Mountain Science, 2022)

Local temperature increases reduce soil microbial residues and carbon stocks - Xiao‐Min Zeng; Jiao Feng; Dai‐Lin Yu; Shu‐Hai Wen; Qianggong Zhang; Qiaoyun Huang; Manuel Delgado‐Baquerizo; Yu‐Rong Liu (Global Change Biology, 2022)
Warming is known to reduce soil carbon (C) stocks by promoting microbial respiration, which is associated with the decomposition of microbial residue carbon (MRC). However, the relative contribution of MRC to soil organic carbon (SOC) across temperature gradients is poorly understood. Here, we investigated the contribution of MRC to SOC along two independent elevation gradients of our model system (i.e., the Tibetan Plateau and Shennongjia Mountain in China). Our results showed that local temperature increases were negatively correlated with MRC and SOC. Further analyses revealed that rising temperature reduced SOC via decreasing MRC, which helps to explain future reductions in SOC under climate warming. Our findings demonstrate that climate warming has the potential to reduce C sequestration by increasing the decomposition of MRC, exacerbating the positive feedback between rising temperature and CO 2 efflux. Our study also considered the influence of multiple environmental factors such as soil pH and moisture, which were more important in controlling SOC than microbial traits such as microbial life‐style strategies and metabolic efficiency. Together, our work suggests an important mechanism underlying long‐term soil C sequestration, which has important implications for the microbial‐mediated C process in the face of global climate change.

Plasma Lipidomic Subclasses and Risk of Hypertension in Middle-Aged and Elderly Chinese - Zhenhua Niu; Qingqing Wu; Yaogan Luo; Di Wang; He Zheng; Yanpu Wu; Xiaowei Yang; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2022)

Vector angle grouping-based solution separation for multipath/NLOS detection and exclusion with the enhancement of doppler test - Jin Chang; Xingqun Zhan; Yawei Zhai; Shizhuang Wang; Kui Lin; Rong Yang (GPS Solutions, 2022)

First report of Pectobacterium colocasium causing bacterial soft rot of taro in Taiwan - Pei-Rong Lin; Chao-Ling Ting; Yun-Ching Sun; Chien-Jui Huang (Journal of Plant Pathology, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Geochronology and geochemistry of the felsic-intermediate dikes from Xiangshan uranium ore field, South China: Implications for petrogenesis, tectonic setting and uranium mineralization - Yong-Jian Wang; Jiang-Tao Nie; Jin-Rong Lin; Hong-Zuo Wang (Mineralogy and Petrology, 2022)

Metabolomics analysis of the potential toxicological mechanisms of diquat dibromide herbicide in adult zebrafish (Danio rerio) liver - Ye Xiao; Xiang Lin; Meilan Zhou; Tianyu Ren; Ruili Gao; Zhongqun Liu; Wenjing Shen; Rong Wang; Xi Xie; Yanting Song; Wenting Hu (Fish Physiology and Biochemistry, 2022)

Correction to: Higher sequestration of wheat versus maize crop carbon in soil under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Microplastic prevalence in marine fish from onshore Beibu Gulf, South China Sea - Jayamini Bimali Koongolla; Lang Lin; Chang-Ping Yang; Yun-Feng Pan; Heng-Xiang Li; Shan Liu; Xiang-Rong Xu (Frontiers in Marine Science, 2022)
In recent years, microplastics have been widely detected in marine fish and may pose potential risks to fish and human health. Even though microplastic pollution is a critical issue, it represents as yet non-quantified threat for some context in the marine environment. In this study, 271 individuals comprising 32 species of marine fish collected from Beibu Gulf were examined for microplastic prevalence, with an aim to provide data on the abundance, physical classification, and chemical characterization of microplastics in the great bay along South China Sea. The results showed that the occurrence rate of microplastics was 93.7%, and the average abundance of microplastics was 1.02 ± 0.18 items per individual (ranging from 0.03 to 4.00 items per individual). Microplastic accumulation was observed with a great variation in different species, body sizes, living habitats, and feeding habits of marine fishes. The dominant polymers identified by μ-FTIR were polyethylene terephthalate and polypropylene. Fibers, smaller sizes (<1 mm), and transparent color were the major characteristics of the detected microplastics, which might be important factors affecting the bioaccumulation. The present study revealed that microplastics in marine fish is a widespread issue in onshore Beibu Gulf.

Recognition of the Multi-class Schizophrenia Based on the Resting-State EEG Network Topology - Fali Li; Lin Jiang; Yuanyuan Liao; Cunbo Li; Qi Zhang; Shu Zhang; Yangsong Zhang; Li Kang; Rong Li; Dezhong Yao; Gang Yin; Peng Xu; et al. (Brain Topography, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Hasubanan alkaloids with anti-inflammatory activity from Stephania longa - Hui Liu; Wan-Qin Liao; Rong-Xiao Lin; Lixia Fan; Jinyan Sun; Hong-Yuan Chen; Fang Liu; An-Ping Yang (Natural Product Research, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Heat Shock Procedure Affects Cell Division-Associated Genes in Gynogenetic Manipulation - Fan Yu; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Pao Xu; Huan Zhong (Marine Biotechnology, 2022)

Reasonable application range of flocculation–solidification combined method in treatment of hydraulically dredged mud slurry - Rong-Jun Zhang; Zhi-Hao Xu; Jun-Jie Zheng; Lin-Wei Tu; Zhan-fang Huang (Marine Georesources & Geotechnology, 2022)

Salicylic acid alleviates selenium stress and promotes selenium uptake of grapevine - Zhiyu Li; Rong Fan; Xuemei Peng; Junjiang Shu; Lei Liu; Jin Wang; Lijin Lin (Physiology and Molecular Biology of Plants, 2022)

Unloading Response Characteristics of Cross Fault Caverns: Effect of Fault Angles - Yong-Hui Shang; Lin-Rong Xu; Yong-Wei Li (Geotechnical and Geological Engineering, 2022)

Structure related α-glucosidase inhibitory activity and molecular docking analyses of phenolic compounds from Paeonia suffruticosa - Po-Chun Chen; Bongani Sicelo Dlamini; Chiy-Rong Chen; Yueh-Hsiung Kuo; Wen-Ling Shih; Yun-Sheng Lin; Chien-Hsing Lee; Chi-I Chang (Medicinal Chemistry Research, 2022)

Higher sequestration of wheat versus maize crop carbon in soils under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Detection of functional and structural brain alterations in female schizophrenia using elastic net logistic regression - Ying Wu; Ping Ren; Rong Chen; Hong Xu; Jianxing Xu; Lin Zeng; Donghui Wu; Wentao Jiang; NianSheng Tang; Xia Liu (Brain Imaging and Behavior, 2022)
Neuroimaging technique is a powerful tool to characterize the abnormality of brain networks in schizophrenia. However, the neurophysiological substrate of schizophrenia is still unclear. Here we investigated the patterns of brain functional and structural changes in female patients with schizophrenia using elastic net logistic regression analysis of resting-state functional magnetic resonance imaging data. Data from 52 participants (25 female schizophrenia patients and 27 healthy controls) were obtained. Using an elastic net penalty, the brain regions most relevant to schizophrenia pathology were defined in the models using the amplitude of low-frequency fluctuations (ALFF) and gray matter, respectively. The receiver operating characteristic analysis showed reliable classification accuracy with 85.7% in ALFF analysis, and 77.1% in gray matter analysis. Notably, our results showed eight common regions between the ALFF and gray matter analyses, including the Frontal-Inf-Orb-R, Rolandic-Oper-R, Olfactory-R, Angular-L, Precuneus-L, Precuenus-R, Heschl-L, and Temporal-Pole-Mid-R. In addition, the severity of symptoms was found positively associated with the ALFF within the Rolandic-Oper-R and Frontal-Inf-Orb-R. Our findings indicated that elastic net logistic regression could be a useful tool to identify the characteristics of schizophrenia -related brain deterioration, which provides novel insights into schizophrenia diagnosis and prediction.

Mechanisms of soil organic carbon stability and its response to no‐till: A global synthesis and perspective - Zheng‐Rong Kan; Wen‐Xuan Liu; Wen‐Sheng Liu; Rattan Lal; Yash Pal Dang; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2022)
Mechanisms of soil organic carbon (SOC) stabilization have been widely studied due to their relevance in the global carbon cycle. No‐till (NT) has been frequently adopted to sequester SOC; however, limited information is available regarding whether sequestered SOC will be stabilized for long term. Thus, we reviewed the mechanisms affecting SOC stability in NT systems, including the priming effects (PE), molecular structure of SOC, aggregate protection, association with soil minerals, microbial properties, and environmental effects. Although a more steady‐state molecular structure of SOC is observed in NT compared with conventional tillage (CT), SOC stability may depend more on physical and chemical protection. On average, NT improves macro‐aggregation by 32.7%, and lowers SOC mineralization in macro‐aggregates compared with CT. Chemical protection is also important due to the direct adsorption of organic molecules and the enhancement of aggregation by soil minerals. Higher microbial activity in NT could also produce binding agents to promote aggregation and the formation of metal‐oxidant organic complexes. Thus, microbial residues could be stabilized in soils over the long term through their attachment to mineral surfaces and entrapment of aggregates under NT. On average, NT reduces SOC mineralization by 18.8% and PE intensities after fresh carbon inputs by 21.0% compared with CT ( p Q 10 ) is observed in NT due to greater Q 10 in macro‐aggregates, an increase of soil moisture regime in NT could potentially constrain the improvement of Q 10 . This review improves process‐based understanding of the physical and chemical mechanism of protection that can act, independently or interactively, to enhance SOC preservation. It is concluded that SOC sequestered in NT systems is likely to be stabilized over the long term.

Mesozoic mafic dykes in the North China Craton: magmatic evolution and implications for gold mineralization - Chao Li; Lin Li; Sheng-Rong Li; M. Santosh; Jun-Feng Shen (International Geology Review, 2022)